Tendency to use the virtual fitting room in generation Y: Results of qualitative study - Miroslaw Moroz (Foundations of Management, 2019)
E-commerce is growing rapidly on a global scale. Among many products purchased via the Internet, clothing is the first in terms of purchase frequency. However, there are growth barriers for this product category, which include, first of all, the client's fear of matching clothing to their own figure or complexion. This results in a high percentage of returns reaching up to 60% of transactions, which is more than that in other e-commerce sectors. One of the possible solutions to the abovementioned problem is the use of a virtual fitting room (VFR), which allows you to try on clothes in terms of size, fit, style, or color on a computer or smartphone screen. The main purpose of the article is to determine the propensity to use a VFR in the age group of generation Y. The second goal is to compare the propensity to use by type of VFR: 2D vs. 3D. The methodology is based on the qualitative exploratory approach. To conduct research, content analysis and sentiment analysis were used. The results of the study indicate that the participants of the research have an ambivalent attitude towards VFR - on the one hand, they perceive VFRs as an interesting solution for Internet users (not only generation Y). On the other hand, however, they themselves show a distance to use the VFR. The analysis also showed that a two-dimensional type of VFR based on augmented reality technology has greater market opportunities.
Keywords: L81; M21; O33; 650; virtual fitting room; virtual dressing room; virtual changing room; e-commerce; clothing industry; generation Y; augmented reality; 3D mapping; human-computer interaction